(untitled) (Research, Society and Development, 2021)
Objective: to describe nursing care for pregnant women with hypertension in primary care. Methods: This is a descriptive study with a qualitative approach in the experience report modality. This being experienced by a student of the Bachelor of Nursing course, during supervised internship I, held at UBSF in a city located in the interior of Bahia. Results: During prenatal consultations, pregnant women diagnosed with GHS were characterized as a great challenge, and of great value for training, which is opportune for the development as a professional future, which brought a lot of learning. Thus, it is worth mentioning that the nurse must be vigilant as to the risk classification in all consultations with pregnant women, thus anamnesis, general physical, gynecological, and obstetric examination, in addition to the promotion of educational activities, are essential. Conclusion: It is evident that there are still some gaps related to the early diagnosis of GHS, which in most cases is a consequence of the late start of prenatal care.